2002
DOI: 10.1139/e01-099
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and orogenic history of a Paleoproterozoic accretionary belt: the Makkovik Province, Labrador, Canada

Abstract: The Makkovik Province is a segment of a Paleoproterozoic accretionary belt (the Makkovik-Ketilidian orogen) that developed on the southern margin of Laurentia at 1.9-1.7 Ga. In contrast to coeval Laurentian orogenic belts that mainly resulted from collision of Archean plates, Makkovikian-Ketilidian orogenesis was dominated by active-margin processes including continental margin arc plutonism and juvenile terrane accretion, both of which were accompanied by regional transpression. In the Makkovik Province, earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 40 publications
4
54
0
Order By: Relevance
“…They proposed that arc accretion was followed by subduction-flip, establishing an ensialic arc on the new margin. This model was supported by Moumblow et al [6], but they rejected a second arc accretion event suggested by Ketchum et al [14], since there is no evidence for two distinct arcs within the Cape Harrison domain.…”
Section: Paleoproterozoic Evolution Of the Sw Grenville Provincesupporting
confidence: 58%
See 2 more Smart Citations
“…They proposed that arc accretion was followed by subduction-flip, establishing an ensialic arc on the new margin. This model was supported by Moumblow et al [6], but they rejected a second arc accretion event suggested by Ketchum et al [14], since there is no evidence for two distinct arcs within the Cape Harrison domain.…”
Section: Paleoproterozoic Evolution Of the Sw Grenville Provincesupporting
confidence: 58%
“…A similar scenario is observed behind the accretionary margin of the Makkovik Province in which the supracrustal units from the Aillik Group were deposited in a retro-arc basin ca. 1.86−1.85 Ga [6,14]. Evidence for a Paleoproterozoic crustal source in the SW Grenville province is further supported by the Kiosk quartzite south of the proposed Penokean arc.…”
Section: Paleoproterozoic Evolution Of the Sw Grenville Provincementioning
confidence: 69%
See 1 more Smart Citation
“…The mixing trend at 2.1 -1.6 Ga shown by the detrital zircon pattern of Figure 5a could correspond to earlier continental arc magmatism at 1.91 -1.70 Ga that reworked Archean crust to the west of the Grenville Province (Makkovikkian; Ketchum et al 2002). The oldest mixing trend, at 2.55 -2.75 Ga (Fig.…”
Section: Discussion Detrital Zircon Signature and Crustal Evolution Omentioning
confidence: 99%
“…This aspect is important to stress, because there are some reconstructions of the Arctic and North Atlantic regions that show North-West Greenland displaced hundreds of kilometres from neighbouring Canada. Such reconstructions -for example those figured by Roest and Srivastava (1989), Eide (2002), Ketchum et al (2002). Wardle et al (2002), Piper and Darabi (2005) and Tessensohn et al (in press) do not explain the lack of displacement in the Precambrian rock units across the Nares Strait.…”
Section: Disposition Of Precambrian Provinces Around Northern Baffin Baymentioning
confidence: 96%